Analysis of Internet Sports Ads Creation Based on Consumption Behavior and Consumption Psychology - Zhuo Bian (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The willingness of users to consume sports changes depending on the types of sports advertisements created. The development of Internet sports advertisements interacts with multiple facets of user sports consumption, including role identification, consumption willingness, and consumer satisfaction. This research examines the production of Internet sports advertisements in light of user psychology and consumption behavior. After extracting the characteristics of Internet-based sports consumption, the authors explained the significance of each characteristic dimension of sports consumption. Then, a stacking model was developed to anticipate consumer psychology, and the modeling procedure was described in detail. In addition, the approach for constructing Internet sports advertisements was described, and customer consuming psychology was grouped using the Gaussian mixture model. The effectiveness of the proposed model was demonstrated through experiments. Based on user behavior and the psychology of sports consumption, this study highlights the design ideas for Internet sports advertisements.